PUBLIC OPINION IN MANAGEMENT RELATIONS: COMMUNICATION ASPECT - Abysova, Maria (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Abstract. The article is devoted to identifying the conditions for the formation of public opinion on the democracy grounds within management relations. The degree of independence, manageability, and dialogicity (monologicity) of public opinion as a set of generally recognized and customary ideas, assessments, and judgments regarding socially significant phenomena, events, etc., is determined by the political regime and traditions of the state. Public opinion in a democratic society is a necessary system element of all-pervasive social communication, which must be taken into account in management activities. The model of deliberative democracy makes it possible to include alternative positions in the public discourse and seek consensus, instead of making decisions monologically. Despite the model of deliberative democracy affirms the inclusiveness, publicity, argumentative nature of public discussions, the requirement of acceptability of the result for all parties, the openness for further revision, etc., it has been criticized. The alternative model of meaningful dissensus instead of the consensus has been offered. The leading principle of dialogue in the formation of public opinion is emphasized. In case of rejection of dialogue, communicative democratic practices, forming public opinion, show similarities with the discursive features of non-democratic regimes: either by approving the majority’s opinion in search of consensus, or by contributing to the growth of fundamentalism in the polyphony of dissensus.